Resources to Explore OJS 3 (PKP Barcelona 2019 Workshop, 2019)
Visit our demo site https://pkp.sfu.ca/ojs/ojs_demo/ Try the test drive site (username: admin; password: testdrive)Look at demos of different OJS themesTake PKP School free online courses and training videoshttps://pkpschool.sfu.ca/Register for a free account to take the coursesReview our documentation and user guidesPKP Documentation Hub: https://docs.pkp.sfu.ca/index.htmlLearning OJS 3: https://docs.pkp.sfu.ca/learning-ojs/en/